COVID-19 related psychosocial problems among university students in Mexico – a longitudinal qualitative examination - Martinez-Torteya, Cecilia; Figge, Caleb J.; Ramírez Hernández, Laura I.; Treviño-de la Garza, Beatriz (Frontiers in Public Health, 2023)
Research on the impact of the COVID-19 pandemic among college students around the world has primarily focused on their mental health symptoms and COVID-specific worry. However, contextually specific understanding of outbreak impacts is key to inform directed public health messaging and programming to improve wellbeing and coping. The current study aimed to identify the main psychosocial problems college students experienced during the first six months of the COVID-19 pandemic in Monterrey, Mexico. Participants were 606 college students (71% female) enrolled in a private university. Participants described COVID-related problems in an open-ended prompt as part of a longitudinal online survey: initially in May 2020, and then every two weeks for 3 months. Thematic analyses were conducted within a longitudinal inductive qualitative approach to rank responses by frequency across themes. Five major categories emerged. At baseline, over 75% of participants noted the outbreak negatively impacted their daily activities and responsibilities, 73% their mental health, 50% their physical health, 35% their interpersonal relationships, and 22% their economic situation. Concerns remained relatively stable throughout the follow-up period, with interpersonal and economic concerns becoming more prevalent as the pandemic progressed. Problems identified in this study can inform preventative measures for future health crises, including tailoring public health messaging and expanding access to contextually sensitive mental and behavioral health programming.